THE IMPROVEMENT OF THE BODY AND UDDER HYGIENE INFLUENCE ON THE MILK SAFETY AND COMPOSITION ON SMALL DAIRY FARMS IN SERBIA - Hristov, Slavča; Mihajlović, Ljubiša; Nakov, Dimitar; Cincović, Marko; Stanković, Branislav (Journal of Agricultural Sciences (Belgrade), 2023)
The hygienic condition of dairy cows and their udders on 128 small size household farms located in different regions of Serbia, predominantly engaged in milk production, 5- 15 cows, lactofreeze and at least one milking machine, were evaluated using a following indicators: 1. general assessment of body cleanliness, 2. visual inspection of teat and udder base, and 3. maintenance of the cleanness of the udder, rated on a scale of 0 and 1 or 1 to 5. The samples were taken after cooling during every visit to the farm and tested for milk protein and fat content, somatic cell count (SCC) and the total number of microorganisms (TNM). The milk fat content was determined by the Gerber method, the protein content by the Kjeldahl method, the TNM according to the ISO 4833-1:2013 method and the SCC using Fossomatic TM. The IBM SPSS program was used for statistical data processing. Capacity, housing system, breed, milking system, number of cows, and capacity occupancy mostly had a very significant or significant impact on hygiene parameters, protein and fat content, SCC and TNM in milk. The hygiene parameters had a continuous trend of improvement in relation to the visits. TNM scores' mean values increased after every visit, with significant differences between visits (F=9.63, P
Keywords: improvement, body, udder, hygiene, milk, safety, composition, small dairy farms